ENHANCING ESP INSTRUCTION THROUGH BLENDED LEARNING: A PEDAGOGICAL MODEL FOR HIGHER EDUCATION - Tohirova Shahribonu Rustamjon qizi (Bright Mind Publishing, 2025)
This scholarly article explores a blended learning model tailored for English for Specific Purposes (ESP) in higher education, focusing on its implementation in Uzbekistan. The model integrates traditional classroom instruction with digital learning environments to improve learner engagement, linguistic proficiency, and professional communication. The research is grounded in sociocultural and task-based learning theories and outlines core elements such as authentic materials, online platforms, and collaborative tasks. It further evaluates a pilot study demonstrating improved ESP outcomes in Uzbek universities, highlighting key implementation strategies and addressing potential challenges. The article concludes by proposing the model as a sustainable framework for modern ESP pedagogy.
Keywords: English for Specific Purposes (ESP), blended learning, higher education, task-based learning, Uzbekistan, digital pedagogy, professional communication, authentic materials, learner autonomy, instructional model.